Christian “Service-Stewardship” and Islamic “Khilafah”: Emerging Models in Educational Administration (American Journal of Islam and Society, 2000)
This article investigates two emerging models in educational administration,namely the Christian “service-stewardship,” and the Islamic“Khilufuh.” The author traces the historical developments and intellectualtraditions within which the current educational administration hasevolved, and the transfoxmation that the discipline has undergone. Thearticle highlights the basic premises, the components of each model,and the implications for educational administration. The juxtapositionof the two models reveals shared elements and divergence. The articleconcludes with a discussion of the potential contribution of the twomodels, as well as the legitimate concerns that should be addressed.